Menoedjoe Repoeblik Bangsawan Dalam Pusaran Kemerdekaan : The role of K.G.P.A.A. Paku Alam VIII & Sri Sultan HB IX in defending Indonesia's Independence (1945-1949): The role of K.G.P.A.A. Paku Alam VIII & Sri Sultan HB IX in defending Indonesia's Independence (1945-1949) - Samudra Eka Cipta (Syntax Corporation Indonesia, 2020)
This study examines the role of a Javanese nobleman and hero from among the royal palaces in an effort to defend Indonesia's independence during the Indonesian revolution of independence. K.G.P.A.A. Paku Alam VIII, then, a representative of the Sultanate of Yogyakarta under Sri Sultan Hamengkubuwono IX together to make Yogyakarta as the territory of the Provisional Government of the Republic when Jakarta was successfully ruled by the Dutch allies. Both figures were also involved in the 1 March 1949 general attack event along with General Sudirman and Suharto in the face of Dutch milier aggression in Yogyakarta. In this study will discuss more specifics on the role of both figures in relation to the Independence Revolution period during the period of 1945-1949.